Investigation on Mechanical Behaviors of Cold Stretched and Cryogenic Stretched Austenitic Stainless Steel Pressure Vessels. (2015) - Lu, Y.Q.; Hui, H.
Abstract: Austenitic stainless steel is widely used in pressure vessels for storage of liquid gas, such as LN2, LO2, LH2 . To make wall thin and weight light, cold stretching technology is applied in cryogenic pressure vessel manufacture. Cold stretching is performed by pressurizing a vessel to a specific pressure and maintaining the pressure for a moment to produce a certain amount of plastic deformation, so that the yield strength of the vessel material could be strengthened after releasing the pressure. Cryogenic stretching is similar in principle to cold stretching, but the medium is liquid nitrogen instead of water in cold stretching. Cold stretching has been recorded in standards such as Cold-Stretching Directions 1991, AS 1210-Supp2-1999, EN 13458-2:2002, EN 13530-2:2002, ASME BPVC VIII-I Code Case 2596, ISO 20421-1:2006, ISO 21009-1:2008. Nevertheless, cryogenic stretching is not applied in pressure vessels manufacture due to lack for detailed investigation. To investigate mechanical behaviors of cold stretched and cryogenic stretched austenitic stainless steel pressure vessels, a series of tests for S30403 were performed at 20°C (temperature in which cold stretching proceeds) and -196°C (temperature in which cryogenic stretching proceeds), the difference of martensite transformation, strength and plasticity in which were compared. Finite element analysis method based on MISO model was used to simulate cold stretching process of pressure vessel, including the process of loading to strengthening pressure, unloading to no-load state and reloading to design pressure. Considering material properties difference, different types of strengthening pressure methods for cryogenic stretching were performed to confirm a rational strengthening pressure value. Mises equivalent stress, tresca equivalent stress, circumferential stress, axial stress and deformation were taken into consideration. The investigation has shown that compared with cold stretching, cryogenic stretching could improve material properties more significantly. In other words, pressure vessels could have thinner wall and lighter weight after cryogenic stretching.